Classification of humeral head pathomorphology in primary osteoarthritis: a radiographic and in vivo photographic analysis - Habermeyer, Peter; Magosch, Petra; Weiß, Christel (Journal of shoulder and elbow surgery, 2017)
Background: The purpose of this study was to characterize the pathologic changes of the osteoarthritic humeral head. Methods: The study included 55 patients with primary osteoarthritis who underwent anatomic shoulder arthroplasty. Several radiologic parameters (radiography, magnetic resonance imaging) were assessed. Humeral head deformity in the transverse plane and humeral cartilage erosion in the coronal plane were chosen for photographic measurements from the resected humeral heads. Results: In the coronal plane, 82% of patients presented with an aspherical humeral head shape with a significantly longer caudal osteophyte. In the transverse plane, 50% of all patients showed a decentered apex. Patients with an aspherical humeral head shape in the transverse plane showed an aspherical humeral head shape in the coronal plane in 94% and a significantly longer osteophyte than patients with spherical humeral head shape, showing a 3-dimensional deformity of the humeral head during progression of primary osteoarthritis. Patients with an osteophyte length between 7 and 12 mm were associated with a glenoid type B2 in 30% and a decentered apex in the transverse plane in 38%. Patients with a humeral osteophyte longer than 13 mm were significantly more frequently associated with a type B2 glenoid (71%; P < .0001) and a decentered apex in the transverse plane in 52%. Conclusion: It seems that the progression of primary osteoarthritis of the glenohumeral joint is characterized by an increasing 3-dimensional deformity of the humeral head related to the glenoid morphology. We therefore propose an extended Samilson-Prieto classification with type A (spherical) and type B (aspherical) and grade I-IV osteophytes.